PERSOALAN BID’AH DALAM BERIBADAH DALAM KONTEKS PENGHAYATAN ISLAM DI MALAYSIA - Ramli, Rushdi (Jurnal Syariah, 2019)
The guideline for performing acts of worship (ibadah) for Muslims is clearly stated in the Quran and the Sunnah. Acts of worship done conforming to these guidelines will enable Muslims to reach a higher spiritual level with their Creator. Islam forbids acts of worship that is bid’ah in nature. Bid’ah more accurately refers to those acts of worship that are practiced and invented based on logic and desire. The inability to distinguish between righteous ibadah and ibadah that is bid’ah in nature has led to many popular ibadah practiced in Malaysia to be branded as bid’ah, even though these acts of worship do not contravene the principles of Islam and the guidelines of the Quran and the Sunnah. Muslims must possess the right knowledge to distinguish between ibadah which is bid’ah in nature from the various acts of worship that its nature is debated by the Muslim scholars.